The proper role of economic liberty and property ownership in a political liberal framework - Place, Joseph Jack (2024)
My thesis engages in the fundamental philosophical discussions of assessing the proper role of property ownership from a political liberal perspective in relation to the moral powers. Property ownership has been claimed as essential to the ability for people to pursue the lives they wish. John Tomasi argued specifically that a protection of the thick economic liberties as basic is essential for the development and exercise of ‘self-authorship’. I argue that John Tomasi’s justification to include a thick collection of property rights in the Rawlsian, or political liberal, scheme of basic liberties is not acceptable, because rather than enhance the moral powers, as argued by Tomasi, the protection would harm them. I argue that Tomasi’s framework harms the pursuit of particular, non-property related conceptions of the good, undermines opportunity for meaningful work and holds a perfectionist conception of meaningful work, and facilitates domination via undermining worker voice and capacity to collectively own property. All of which harms the moral powers. However, my argument raises fundamental issues against the typical Rawlsian argument and framework. Rawls’ frameworks also fail to offset domination, and has a similarly perfectionist conception of meaningful work, and either ignores the importance of worker voice and collective ownership within a property-owning democracy or undermines the capacity to privately own property within liberal socialism. The property-owning democracy model is also unable to handle new technological challenges to the moral powers from artificial intelligence and the resulting work polarisation. I develop a more anti-perfectionist idea of meaningful work, which factors freedom from domination, and consider the importance of worker voice and capacity to collectively and privately own property, to reject the typical property-owning democracy and liberal socialist models alongside Tomasi’s market democracy. I argue that a framework which best assists in the development of the moral powers must not protect economic liberty as basic, however, it should permit some private ownership, alongside a strong protection of worker voice and capacity for collective ownership.